ESG Disclosure Comparison Analysis in the Fast-Moving Consumer Goods Industry - Michelle Chin Lee Yan; Isna Putri Rahmawati (Jati: Jurnal Akuntansi Terapan Indonesia, 2025)
This article analyses the disclosure of ESG (Environmental, Social, and Governance) practices in Fast-Moving Consumer Goods (FMCG) companies that are listed on the Indonesia Stock Exchange in 2023. This study employed a descriptive analysis approach to describe the level of ESG disclosure in the Indonesian FMCG sector. The research sample included 20 FMCG companies that are listed on the Indonesia Stock Exchange in 2023. The results showcased that ESG disclosure in Indonesian FMCG companies, based on the Global Reporting Initiative (GRI) Standard, has reached a pretty good level. The average quantity of ESG disclosures was 57.39%, with details of environmental aspects at 51.61%, social aspects at 60.62%, and governance aspects at 60%. These findings reflect that although ESG disclosures in the Indonesian FMCG sector have reached an adequate level, there remains potential improvement, particularly regarding the disclosure of environmental aspects.